Longer-term oral antiplatelet use in stable post-myocardial infarction patients: Insights from the long Term rIsk, clinical manaGement and healthcare Resource utilization of stable coronary artery dISease (TIGRIS) observational study. (1st June 2017) - Goodman, Shaun G.; Nicolau, Jose C.; Requena, Gema; Maguire, Andrew; Blankenberg, Stefan; Chen, Ji Yan; Granger, Christopher B.; Grieve, Richard; Pocock, Stuart J.; Simon, Tabassome; Yasuda, Satoshi; Vega, Ana Maria; et al.
Abstract: Objective: To describe contemporary patient characteristics and treatment patterns, including antithrombotic management, of post-myocardial infarction (MI) stable coronary artery disease (CAD) patients at high atherothrombotic risk from different geographical regions. Methods: Patients ≥ 50 years with prior MI 1–3 years ago and ≥ 1 risk factor (age ≥ 65 years, diabetes, 2nd prior MI > 1 yr ago, multivessel CAD, creatinine clearance 15–<60 ml/min) were enrolled by 369 physicians (96% cardiologists) in 25 countries (2013–14) in the prospective TIGRIS study (NCT01866904). Results: 9225 patients were enrolled (median 1.8 years) post-MI: 52% with prior ST-elevation MI, median age 67 years, 24% women, 67% Caucasian, 55% had ≥ 2 additional qualifying risk factors, 14% current smokers, 67% overweight/obese, 34% with blood pressure ≥ 140/90 mm Hg. 81% underwent percutaneous coronary intervention (PCI; 66% with drug-eluting stents) for the index MI. 75% of patients had been discharged on dual antiplatelet therapy (DAPT; acetylsalicylic acid [ASA] + ADP receptor inhibitor [ADPri]), mainly clopidogrel (75%). 63% had discontinued antiplatelet treatment (60% ADPri) around 1 year, most commonly by physician recommendation (90%). At enrolment, 97% were taking an antithrombotic drug, most commonly ASA (88%), with 27% on DAPT (median duration 1.6 years); continued DAPT > 1 year was highest (39%) in Asia-Pacific and lowest (12%) in Europe. Conclusions: Despite guideline recommendations, 1 in 4 post-MI patients did not receive DAPT for 1 year. In contrast to guideline recommendations supporting newer ADPris, clopidogrel was mainly prescribed. Prior to recent RCT data supporting DAPT > 1 year post-MI/PCI, > 1 in 4 patients have continued on DAPT, though with substantial international variability.